Using CNNs for Quality Assessment of No-Reference and Full-Reference Compressed-Video Frames - da Silva, Renato; Brito, Luiz; Albertini, Marcelo; do Nascimento, Marcelo; Backes, André (Anais do Workshop de Visão Computacional (WVC), 2020)
For videos to be streamed, they have to be coded and sent to users as signals that are decoded back to be reproduced. This coding-decoding process may result in distortion that can bring differences in the quality perception of the content, consequently, influencing user experience. The approach proposed by Bosse et al. [1] suggests an Image Quality Assessment (IQA) method using an automated process. They use image datasets prelabeled with quality scores to perform a Convolutional Neural Network (CNN) training. Then, based on the CNN models, they are able to perform predictions of image quality using both Full- Reference (FR) and No-Reference (NR) evaluation. In this paper, we explore these methods exposing the CNN quality prediction to images extracted from actual videos. Various quality compression levels were applied to them as well as two different video codecs. We also evaluated how their models perform while predicting human visual perception of quality in scenarios where there is no human pre-evaluation, observing its behavior along with metrics such as SSIM and PSNR. We observe that FR model is able to better infer human perception of quality for compressed videos. Differently, NR model does not show the same behaviour for most of the evaluated videos.